Metal Concentrations in Human Pancreatic Juice - Ishihara, Nobuo; Koizumi, Masaru; Yoshida, Arata (Archives of Environmental Health: An International Journal, 1987)
Concentrations of 11 metals (cadmium [Cd], lead [Pb], copper [Cu], iron [Fe], manganese [Mn], cobalt [Co], chromium [Cr], nickel [Ni], zinc [Zn], magnesium [Mg], and calcium [Ca]) and protein in human pancreatic juice were studied. Human pancreatic juice was sampled by endoscopic cannulation after administration of secretin (intravenous [i.v.], 1 μ/kg). There were 19 subjects (11 males and 8 females) and the means of their ages were 50.3 yr (male, 20-68 yr) and 52.5 yr (female, 45-64 yr). Diagnoses were: normal, 5; early pancreatic cancer, 9; and chronic pancreatitis, 5. None had symptoms suggestive of disturbances in endocrine and exocrine functions of the pancreas. Concentrations of metals and protein in pancreatic juice did not change significantly between males and females or with pathological changes in the pancreas. Assuming the flow rate of pancreatic juice to be 1500-2000 ml/day, the daily excretions of metals into duodenum via pancreatic juice were calculated as follows (μmoles of metal/day): Cd, 0.012-0.012; Pb, 0.216-0.288; Cu, 6.20-8.26; Fe, 2.34-3.12; Mn, 0.100-0.133; Co, 0.165-0.220; Zn, 7.46-9.94; Cr, 0.084-0.112; Mg, 274.1-365.4; Ni, 1.64-2.18; and Ca, 0.221-0.295. Toxic (Cd and Pb) and essential metals (Cu, Zn, Fe, Mn, Cr, and Ni) are excreted daily into duodenum via pancreatic juice.